Integrated Boarding Systems University: An Effective Formula for Creating a Good Man - Firda Inayah (At-Ta'dib, 2024)
This article aims to explain the educational structure at UNIDA Gontor as a Boarding system University. This system is considered both appropriate and effective as a solution to the problem of the Westernization of Islamic education and as an effort to realize the Islamization of knowledge. This study employs a qualitative research design. To address the subject matter, the researcher uses a philosophical approach and an analytical descriptive method. The study concludes that the integration of the university and pesantren educational systems expands the essence and scope of the curriculum. The essence of the curriculum encompasses not only academic education with a range of courses but also non-academic education shaped by the pesantren system, designed beyond classroom activities. Furthermore, the integration of these two curricula in practice involves various activities, including formal, informal, and non-formal education, all of which are structured to instill an Islamic worldview. This holistic system is envisioned as a means of revivalism and the reformulation of a unique new system for the resurgence of Islamic universities, serving as a medium for the emergence of the insān al-kāmil (the complete human), in alignment with the true objectives of Islamic education.